Penyegaran Kemampuan Guru dalam Merancang Media Pembelajaran Melalui Aplikasi Powtoon dan Screencast O Matic - Marlena, Novi; Dwijayanti, Renny; Patrikha, Finisica Dwijayati; parjono, Parjono; Sudarwanto, Tri (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
The lack of technology and information utilization in the making of learning media by teachers is the main factor in this community service activity. It is a challenge for teachers to create an interactive and varied learning media that can stimulate students to be more active, stimulate students' critical and creative thinking. To increase students' concentration and interest is audio-visual media, which is able to stimulate their senses of sight and hearing together. This designing audio-visual learning media based IT training uses the Powtoon application and the Screencast O Matic application. Direct and mentoring training made it easier for teachers to produce interesting and interactive learning media based on audio-visual. The aims of this training in community service are 1) provide teachers' knowledge and understanding of the nature of learning media, 2) developing audio-visual media training uses Powtoon application and Screencast O Matic application, 3) provide assistance related to audio-visual learning media based IT. The subjects in this community service are vocational high school teachers in Bangkalan and members of MGMP Otomatisasi Tata Kelola Perkantoran (OTKP). The implementation of this community service uses a variety of lecture methods, discussions, question and answer, direct tutorials and direct practice of making an audio-visual learning media based IT. The result of this community service are that most trainees are able to practice and design learning media from the learning subjects using Powtoon or Screencast O Matic application.